Surface-enhanced Raman scattering labeled nanoplastic models for reliable bio-nano interaction investigations - Zhang, Panpan; Wang, Yunqing; Zhao, Xizhen; Ji, Yunxia; Mei, Rongchao; Fu, Longwen; Man, Mingsan; Ma, Jiping; Wang, Xiaoyan; Chen, Lingxin (Journal of hazardous materials, 2022)
Nanoplastics (NPs) have attracted great attention as an emerging pollution. To date, their interaction with biological systems has been studied mostly by using fluorescent-labeled NPs, which suffered from serious drawbacks such as biological autofluorescence interference and false-positive results. Reliable optically labeled NP models are eagerly desired until now. Herein, a novel near-infrared (NIR) surface-enhanced Raman scattering (SERS) labeled NP model was proposed, which gained single-particle ultra-sensitivity, deep tissue detection, multiplex labeling ability, and anti-interference property. More importantly, the NP demonstrated satisfactory in vivo signal stability which completely prevented the positive-false problems. The advantages of the NPs enabled direct, dynamic in vivo behavior imaging study in living zebrafish embryo, adult zebrafish and green vegetable Brassica rapa. It was found for the first time that NPs entered blood circulation system of zebrafish larva via dermal uptake route, which only occurred in a short 48 h-window post-hatch. NPs widely distributed in roots, shoots and leaves of Brassica rapa seedlings germinating and growing in the NP-containing hydroponic culture. Different depths of one root showed varied adsorption capabilities towards NPs with fulvic acid, lipid and sodium dodecyl sulfate eco-coronas. This work provided an ideal tool for reliable bio-NP interaction study for a variety of organisms, which could promote the research of NPs. [Display omitted] •SERS tag-labeled nanoplastics (NPs) show ultra-sensitivity, signal stability and multiplex labeling ability.•NPs can enter blood circulation system of zebrafish larva via a dermal uptake route.•The digestive tract and gill were dominant accumulation sites in adult zebrafish.•NPs distribute in roots, stems and leaves of Chinese cabbage seedlings germinating and growing in hydroponic culture.